Industrial organization - Baye, Michael R. 1958- (Emerald, 2000)
Volume 9 is entitled Industrial Organization and is the ninth volume in the series Advances in Applied Microeconomics. This series provides a forum in which researchers may disseminate frontier research in applied microeconomics to include both theoretical and empirical contributions in applied areas such as industrial organization, consumer and producer behavior, public economics, natural resources, and other applied microeconomic fields. Volumes are published along themes and contain theoretical papers that apply state-of-the-art theory to model important real-world phenomenon, as well as empirical papers that examine such phenomenon.